Tepidibacter aestuarii sp. nov., isolated from the Bach Dang Estuary, Haiphong, Vietnam - Pradel, Nathalie; Chifflet, Sandrine; Beavogui, Angelina; Bartoli, Manon; Chu Van, Thuoc; Aouane, Aicha; Bui Van, Vuong; Mari, Xavier; Pham The, Thu; Oliveira, Pedro H; Cayol, Jean-Luc (International journal of systematic and evolutionary microbiology, 2024)
A mesophilic, anaerobic, endospore-forming, fermentative bacterium designated strain 8C15b was isolated from bank sediment of the Bach Dang Estuary, Haiphong, Vietnam. The Bach Dang Estuary, where Haiphong harbour is located, is subject to strong anthropogenic influence, resulting in high concentrations of black carbon and heavy metals. Strain 8C15b grew optimally at 30 °C, pH 7.5 and with 2.5 % (w/v) NaCl. The main cellular fatty acids consisted of iso-C (51 %), iso-C ω7 (32 %) and iso-C (5 %). Genomic considerations of strain 8C15b and comparisons with the phylogenetically closest strains of the genus provide evidence that SC562 (=DSM 15285 ), DV1184 (=DSM 15518 ), B1 (=JCM 16806 ) and strain 8C15b could be differentiated at the species level. We propose the name sp. nov. for the type strain 8C15b (=JCM 35983 =KCTC 25692 ). Finally, the nickel-tolerance properties of strain 8C15b are highlighted in this study.